Building a Bridge from Papermaking to Solar Fuels. (3rd September 2019) - Jiang, Zaiyong; Zhang, Xinhan; Sun, Wei; Yang, Deren; Duchesne, Paul N.; Gao, Yugang; Wang, Zeyan; Yan, Tingjiang; Yuan, Zhimin; Yang, Guihua; Ji, Xingxiang; Chen, Jiachuan; et al.
Abstract: Black liquor, an industrial waste product of papermaking, is primarily used as a low‐grade combustible energy source. Despite its high lignin content, the potential utility of black liquor as a feedstock in products manufacturing, remains to be exploited. Demonstrated here in is the use of black liquor as a primary feed‐stock for synthesizing graphene quantum dots that exhibit both up‐conversion and photoluminescence when excited using visible/near‐infrared radiation, thereby enabling the photosensitization of ultraviolet‐absorbing TiO2 nanosheets. In addition, these graphene quantum dots can trap photo‐generated electrons to realize the effective separation of electron‐hole pairs. Together, these two processes facilitate the solar‐powered generation of H2 from H2 O, and CO from H2 O–CO2, using broadband solar radiation. Abstract : Schwarzlauge, ein industrielles Abfallprodukt der Papierherstellung, wird meist als minderwertiger brennbarer Energieträger eingesetzt. Die Synthese von Graphenquantenpunkten (GQDs) mit Schwarzlauge als Vorstufe wird nun vorgestellt. Die GQDs weisen eine ausgezeichnete Aktivität in der Ab‐ und Aufwärtskonversion der Photolumineszenz auf, was genutzt werden kann, um die photokatalytische Aktivität von TiO2 in der H2 O‐ und CO2 ‐Reduktion zu verbessern.